Numerical analysis of MHD tri-hybrid nanofluid over a nonlinear stretching/shrinking sheet with heat generation/absorption and slip conditions - Zafar Mahmood; Sayed M Eldin; Khadija Rafique; Umar Khan (Alexandria Engineering Journal, 2023)
In light of the exciting potential of nanofluids, this work presents a new mathematical model for enhancing heat transfer using tri-hybrid nanofluids. In this study, the influence of heat production/abstraction and mass suction on MHD stagnation point flow in a nonlinearly stretching/shrinking sheet of a tri-hybrid nanofluid based on water is investigated. Boundary conditions based on the Maxwell velocity slip and the Smoluchowski temperature are also considered. We shall model the flow-control equations based on our assumptions. An ordinary differential equation system may be constructed from nonlinear partial differential equations for which a similarity transformation does not provide an exact solution. In MATHEMATICA 10, the shooting with Runge-Kutta (RK-IV) technique will be used to solve the reduced equations analytically. There were charts and figures showing how different variables affected the speeds of motion, temperature, skin friction coefficient, and local heat transmission. The characteristics of volume fraction, mass suction, magnetic field, and stretching all contribute to the acceleration of nanoparticles. When the nanoparticle volume fraction and heat production parameters increase, the temperature profile improves, but the mass suction, magnetic, and stretching parameters decrease. Compared to ordinary fluid, the Nusselt number reveals an improvement of around 9.8% for nanofluid, 19.85% for hybrid nanofluid, and 44.04% for tri-hybrid nanofluid when the strength of S is raised from 2.0 to 2.4. The heat transfer rate of the tri-hybrid nanofluid is also superior to that of the hybrid nanofluid and the traditional nanofluid. Results from this study were compared to those already in the literature, and they were determined to be quite consistent. Many other fields might benefit from this study, including those dealing with extreme heat or cold, aerospace technology, medicine, metal coatings, and biosensors.